Determination of Epidermal Growth Factor and Interleukin 6 in Patients with Atopic Dermatitis in karbala Province - Hameed, Zahraa Ch (Technium BioChemMed, 2024)
The most prevalent chronic skin inflammatory illness, Atopic Dermatitis (AD), significantly lowers the quality of life for those who suffer from it. The clinical course, age at onset, and degree of allergy and non-allergic comorbidities associated with AD vary widely. Epidermal growth factor receptor controls a number from keratinocyte processes, including as migration, adhesion, survival, and differentiation. The contrast between differentiation and cell cycle progression is one of these pleiotropic effects that stand out. Also, Interleukin 6 promotes the healing of corneal epithelial wounds. These cytokines may cause corneal neovascularization because they affect different kinds of cells. measurement the concentrations of EGF and interleukin 6 in the serum of men with Atopic Dermatitis and its correlated with severity of the disease. Serum Samples for the current study were collected from 60 serum samples from men with Atopic dermatitis and 60 samples from the control group. All samples were collected from outpatient dermatology clinics in karbala province. The ages of all men ranged between 28 years and 40 years. By ELISA kits, the epidermal growth factor concentrations and interleukin 6 were measured in serum). Results showed significantly increased in levels of EGF and interleukin 6 (p< 0.05) in patient with Atopic Dermatitis compared with control group. These findings imply that EGF might, in an inflammatory setting, collaborate with other cytokines to strengthen the immunological barrier, The pathophysiology of dermatitis is significantly influenced by IL6, and the clinical severity of AD disease development is correlated with elevated levels of this protein.